Magnetic resonance imaging in primates. The example of the mouse lemur (Microcebus murinus): From detection of pathological aging to therapeutic evaluations - Nelly Joseph-Mathurin; Olene Dorieux; Audrey Kraska; Anne Bertrand; Mathieu Santin; Nadine El Tannir El Tayara; Marc Dhenain (Revue de Primatologie)
Cerebral aging is a major public health issue in our societies as the aged population increases dramatically. It leads in many cases to neurodegenerative diseases such as Alzheimer disease (AD). Rodents and particularly transgenic mice are widely used as models for research on physiopathology of cerebral aging, neurodegenerative diseases and for the evaluation of therapies. However these models do not mimic all the pathophysiological aspects of human diseases. Complementary models such as non-human primates are phylogenetically close to humans and thus more predictive of drug efficiency in humans. Mouse lemur (Microcebus murinus) is a small primate (about 12cm, 100g) described as a useful model of cerebral aging and as a potential model of AD. Indeed several animals develop age-associated cerebral alterations like amyloidosis and other cerebral changes. Non invasive medical imaging methods such as magnetic resonance imaging (MRI) can be used to follow-up brain changes in these animals. In this review, we present how mouse lemurs can be followed-up by MRI and how MRI can be used during therapeutic evaluations and other applications in this model. MR images can be used to follow-up cerebral anatomy in mouse lemurs. It allows for the description of age-associated atrophic processes, age-associated iron accumulation, and vascular anatomy (thanks to MR angiography). Cerebral glucose uptake can be studied in mouse lemurs with other in vivo imaging modalities such as positron emission tomography (PET). In this case, MRI can be used as a support for quantification of radioligand uptake in specific structures. Ex vivo MR imaging is another MR protocol that can be used to describe cerebral aging in lemurs. It provides high resolution 3D histological brain images and allows for studying exquisite anatomical details or microhemorrhages. Finally, MRI can be used to practice cerebral surgery in lemurs and determine coordinates for stereotactic injections. It can also be used during therapeutic interventions by selecting animals to be involved in therapeutic trials and also by following specific MR biomarkers. MRI is thus critical to better characterize cerebral aging in the mouse lemur and to better carry out longitudinal studies in this primate model.